Evaluating Traffic Operation for Multilane Highway (Ramadi – Fallujah) Highway as Case Study (Iraqi Journal of Civil Engineering, 2013)
Multilane highways typically are located in suburban communities, leading into central cities, or along high-volume rural corridors connecting two cities or significant activities that generate a substantial number of daily trips. The objectives of the present study include the analysis, and evaluation the level of service (LOS) on section for multilane highway in Ramadi city. The LOS multilane highway is based on density, which is calculated by dividing per lane flow by speed. The required traffic and geometrical data has been collected through field surveys on the section for multilane highway. Traffic volume data were collected manually and classified by vehicles types during each 15 minute interval. Highway Capacity Software 2000 (HCS 2000) program is used for the requirements of traffic analysis process to determine the level of service. It has concluded that the level of service on selected section for east bound is (A), and for west bound is (B).